The geographic patterns of the exceptional longevity in Croatia - Mašanović, Marija (Array, 2009)
Summary: The aim of this study was to provide an overview of the exceptional longevity patterns in Croatia. The prevalence of nonagenarians (aged 90 years or more) and centenarians (100 years or more) was calculated from the 1953–2001 census data. The data were analyzed with chi-square test and trend analysis. The results indicate steady and significant increasing trends in both age groups, more pronounced in women. Geographical distribution of the exceptional longevity had a clear coastline-to-mainland gradient, with higher prevalence of exceptionally old people in the coastal parts of the country. Additionally, exceptionally old respondents from the Croatian Adult Health Survey (CAHS) were compared to elderly ones (65–89 years old). The results suggested that exceptionally old respondents had lower prevalence of overweight and obesity and lower blood pressure, thus exhibiting strong survivor phenomenon. At the same time, exceptionally old respondents from the CAHS had higher prevalence of confirmed hypertension in medical history and reported taking blood pressure medication more often. The results of this study suggest that the pattern of exceptional longevity in Croatia has a clear coastline-to-mainland gradient, which is likely to be associated with the different lifestyle and dietary patterns between these two populations